Integrating Literacy into Reading Instruction - Shuai Ma; Erwin Gay; Yan Liu (EDU Journal - English Department of UMMU Journal, 2022)
Abstract: Reading achievement is considered an essential aspect of learners' literacy. Life could be challenging for immigrants who are newcomers to the U.S. with limited literacy skills. This study explores the challenges an adult ESL immigrant student faces when taking ESL classes and the reading strategies the learner uses to make sense of the reading materials. The researchers use a qualitative approach based on the theory of case study. This case study gives insights into how a student engages with complex tests through practical metacognitive strategies and cognitive strategies. Results indicate that the learner can apply some cognitive and metacognitive strategies, like making connections using prior knowledge, but using strategies is limited. The subject lacks cognitive and metacognitive strategies like handling new unknown words and summarizing. There was a positive gain regarding strategy use after the training. Results also suggest that the challenges for Adult ESL immigrant learners need more motivation, availability, resources, and funding. It provides practical pedagogical implications in language learning and teaching for Adult ESL immigrant learners. Keywords: adult ESL; reading comprehension; immigrant; challenges